Assessing Cadet Cybersecurity: Simulated Rogue Access Point Attacks at Peruvian Air Force Academy - Tapia Ochoa, David Gerardo; Alzamora de los Godos Urcia, Luis Alex; Valladolid Marcos, Fiorella Sthefany; Calderón Saldaña, Jully Pahola; Aguilar Suares, Marlene Pilar; Aparicio Fernández, María Fanny; Pineda Medina, Javier Alejandro (LACCEI, 2025)
Abstract —This study explores the deployment of Rogue Access Points (Rogue APs) with realistic attack templates to assess cybersecurity vulnerabilities among cadets at the Peruvian Air Force Academy. Given the growing threat that Rogue APs pose to military networks, the research underscores the need to strengthen cadets’ cybersecurity training. A structured methodology was employed to design and implement realistic attack scenarios that replicate potential weaknesses in wireless networks. Through penetration testing exercises, the study evaluates cadets’ ability to detect, respond to, and mitigate these threats. The findings suggest that incorporating Rogue APs into training programs significantly improves cadets’ situational awareness and reaction times, equipping them with essential skills for real-world cyber defense.